The Encounter of Christianity With The Old Religion of Minahasa - Ramli Sarimbangun (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this article is to conduct an in-depth analysis of the encounter between Christianity and the old Minahasa religion. The problems related to the revival and re-existence of the old Minahasa beliefs affect the congregation's faith in Minahasa today. The method to solve this problem is qualitative research, which involves collecting scientifically tested literature, such as books and journals, without neglecting field data. Through this discussion, the author offers a new perspective that the old Minahasa religion needs to be studied critically and constructively to highlight its local wisdom to enrich theological efforts in the Evangelical Christian Church in Minahasa. A conclusion that confirms that the goal has been achieved and the problem has been answered. This study concludes that the manguni bird symbolizes the fusion of Christianity and Minahasa old traditions that illustrate the identity of salvation and the church's role as the guardian of truth. Progressivity in Minahasa is not only caused by GMIM or the influence of Protestantism but also by actual theological teachings that affect life attitudes based on the foundation of the Bible and GMIM confession of faith; the Manguni bird as a symbol of GMIM represents religious values,  historical, sociological, and anthropological as well as the role of the church in building contextual theology, there is a hereditary call to preserve nature and build Minahasa culture based on biblical teachings with the duty to fellowship and serve amid the diversity of society.